A compact transparent polarization-insensitive metasurface with broadband monostatic and bistatic radar cross-section reduction of millimeter-waves. (1st September 2022) - He, Xiaoluo; Qi, Chu; Wong, Alex M H
Abstract: This paper proposes an optimized optically transparent metasurface (OTM) which achieves broadband monostatic and bistatic radar cross-section (RCS) reduction with polarization and angle insensitivity. Through employing (a) theoretical formulation involving both monostatic and bistatic RCS and (b) unit cell placement optimization using the particle swarm optimization approach, we achieve monostatic and bistatic RCS reduction over a broad bandwidth with a single-layer, ultra-thin metasurface featuring only two types of unit cells. The proposed metasurface has high optical transparency and electrically small size compared to counterparts with similar performances. Simulation and experimental measurement show that the metasurface achieves more than 10 dB monostatic and bistatic RCS reduction from 18 to 34 GHz, which completely covers the 5G mm-wave spectrum. The proposed optically transparent metasurface can find use in many areas, including mm-wave applications, invisible glass technology, and vehicle windshield systems.